Circulating inflammatory biomarkers and endocrine responses to exercise in female soccer players - Janikowska, G.; Kochanska-Dziurowicz, A.; Pokora, I.; Zebrowska, A. (Journal of Human Kinetics, 2020)
The objective of the study to determine the effects of graded exercise on the cytokines and insulin-like growth factor-1 (IGF-1), growth hormone (hGH), testosterone (T), and cortisol (C) concentrations in the peripheral blood of female soccer players, and to evaluate if increased inflammatory biomarkers were related to these hormones and performance variables. Sixteen female soccer players (N = 16, age 19.3 ± 2.3 years) participated in this study. Blood samples were collected at three time points: pre-exercise, post-exercise, and in the 15th minute of recovery, to evaluate morphological and biochemical variables. The relative expression of IL-6 (interleukin 6) and serum concentrations of the cytokines were increased in the recovery period compared to pre-exercise levels (p = 0.03 and p=0.005, respectively). There was a significant effect of exercise on serum hGH level (p " 0.001), T/C ratio (p = 0.001), and C level (p=0.02). Positive correlations were found between: post-exercise IL-1ß (interleukin 1 beta) and IL-6 (R = 0.84, p = 0.000), and the IL-6 and TNF-a (tumor necrosis factor alpha) gene expression during recovery (R = 0.65, p = 0.009), and serum IL-1ß post-exercise and maximal power (R = 0.68; p = 0.004). Exercise-induced serum C levels positively correlated with IGF-1 levels (R = 0.52 p = 0.05). Negative associations were revealed between post-exercise T/C ratio and IGF-1 (R = - 0.58, p = 0.03) and serum free T and IL- ß (R = -0.56, p = 0.04) levels. The low level of pre-exercise genes and protein of the IL-1ß, IL-6 and TNF-a indicate a lack of inflammation signs in the female soccer players. This study shows significant effects of exercise on hormone levels and pro-inflammatory markers, which could be used to identify the role of female sex steroids on the immune function.